(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
An integral part of UCC’s institutional vision and mission is Whole-Person Education, a large part of which is subsumed under holistic wellness. The researchers determined the level of holistic wellness of JHS students, SEAS students, and faculty pre-pandemic and during the pandemic and compared the level of holistic wellness among these three groups as well as in terms of sex, religious affiliation, type of community, and family income. . The study used cross-sectional research design as it described the status of holistic wellness among the respondents and determined their differences in the phenomenon being studied, given the different profile variables. The respondents of the study were students and faculty members from the Junior High School and the School of Education, Arts, and Sciences. The main data gathering tool was an adopted questionnaire from Smith (2008). The data were treated using the total scores of the respondents to determine health status, a paired sample t-test to compare pre-pandemic and during pandemic holistic wellness, and ANOVA and Kruskall-Wallis to compare the three groups for significant differences, including significant differences in terms of gender, religious affiliation, type of community, and family income. . Overall, the respondents had a good health status in terms of their general well-being. Also, they fared well in the different dimensions, such as mental and emotional (highest), spiritual and social, and physical and environmental (lowest). The respondents had a significantly better wellness status before the pandemic than during the pandemic. The faculty was significantly higher than the SEAS students in terms of mental and emotional health. There were no significant differences among the three groups in terms of general well-being and the other specific dimensions of health. There were no significant differences in the level of holistic wellness in termsof sex, religious affiliations, type of community living in, and family monthly income. The researchers recommend revisiting the continuity plan for both schools to explore how the holistic wellness of the junior high school students, pre-service teachers, and faculty members can be supported and enhanced. Furthermore, the coverage of the study is recommended to be expanded to the entire College to develop an enhanced institutional wellness program for all stakeholders.